Association of Fungi with Breadfruit (Artocarpus altilis Fosb.) (Journal of Bangladesh Academy of Sciences, 2012)
Nine species of fungi belonging to eight genera of Deuteromycetes were found associated with leaves and fruits of breadfruit, Artocarpus altilis. The fungi were Alternaria alternata (Fries) Keissler, Aspergillus niger Van Tiegh, Aspergillus flavus Link, Colletotrichum gloeosporioides (Penz.) Sacc, Curvularia lunata (Wakker) Boedijn., Penicillium sp. Pteroconium state of   Apiospora camptospora Penz. & Sacc. and Spicaria sp., and Zygosporium oscheoides Mont.. This is the first report of association of A. alternata, C. gloeosporioides., Curvularia lunata,  Penicillium sp. Pteroconium state of A. camptospora, Spicaria sp. and Z. oscheoides, with breadfruit. Colletotrichum gloeosporioides was the predominating fungus recorded on all infected matured leaves showing brown lesion and anthracnose symptom, and also pathogenic to breadfruit plant. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10930 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 143-146, 2012